Blockchain Technology in support of the Brazilian Navy logistics and budget control system - Siqueira, Philippe Tavares Alves de (2020)
Blockchain technology is a contemporary phenomenon that brings new perspectives to a diversity of fields that can benefit from its characteristics of transparency and reliability. The purpose of this thesis is to explore some potential applications of this technology within the Brazilian Navy’s (BN) supply chain management and budget control processes, contributing to a more efficient public administration. Through case studies, the thesis aims to unpack the complexity of blockchain applications, explore U.S. Department of Defense and industry application patterns, collect data related to successful implementations of this technology, and analyze the possibility of its implementation for the BN. There are certain limitations to its application, such as the relative immaturity of this technology and paucity of case studies in Brazil, and a lack of regulation regarding blockchain adoption in Brazil. Overall, this study suggests a pilot program to integrate the BN logistics and budget control systems on a blockchain platform to better manage multi-party transactions and support the decision-making process. The objective is to render the BN savings in time and dollars, permitting the optimization of warfighter support. On the side of the budgetary system, it would help automate cost estimates, track specific projects’ expenses, identify the actual allocation of funds, and provide a trustable historical record.